Optimalisasi Peran Rimbawan Muda Dalam Pengelolaan Taman Nasional Gunung Ciremai Dan Implikasinya Terhadap Ketahanan Wilayah (Studi di Balai Taman Nasional Gunung Ciremai Kuningan, Jawa Barat) - Nurhalida Yogaswara; Edhi Martono; Djaka Marwasta (Universitas Gadjah Mada, 2017)
ABSTRACT This research examined the optimization of the role of young foresters in the management of Ciremai Mountain National Park (TNGC) and its implications for regional resilience (Studies in the National Park of Mount Ciremai Kuningan, West Java). The purpose of this research aimed to analyzed the optimization of the role of the young foresters in the management of TNGC, as well as to analyzed the implications of optimization the role of a young forester resilience in the region surrounding villages and areas along TNGC itself.Descriptive qualitative had been used and the data was collected based on in-depth interviews with research participants and deeper observation in the field. And also the data relied thoroughly on published data and academic journals or papers and also documentation. Data analysis techniques in this study, namely: 1) data reduction, presentation of data, Interpretation, and withdrawal conclusion.The results showed that linked to optimization of the role of young foresters in conservation management efforts TNGC still seemed to clashed with the economic needs of society that had not been completely fulfilled by switching professions to became the organizer and environmental services since Mount Ciremai in charge as a National Park. Related to optimized the role of a young forester implications for the resilience of the region there was still an imbalance in the respective aspects such as ecological, economic, social and cultural rights of rural areas around the region and from the region TNGC itself.ABSTRAKPenelitian ini mengkaji tentang optimalisasi peran rimbawan muda dalam pengelolaan Taman Nasional Gunung Ciremai (TNGC) dan implikasinya terhadap ketahanan wilayah (Studi di Balai Taman Nasional Gunung Ciremai Kuningan Jawa Barat). Adapun tujuan dalam penelitian yaitu untuk menganalisis optimalisasi peran rimbawan muda dalam pengelolaan TNGC, serta untuk menganalisis implikasi optimalisasi peran rimbawan muda terhadap ketahanan wilayah di desa sekitar TNGC dan wilayah kawasan TNGC itu sendiri. Metode yang digunakan oleh peneliti dalam penelitian ini adalah metode deskriptif kualitatif. Teknik pengumpulan data dilakukan dengan wawancara mendalam, dengan observasi lapangan, jurnal akademik dan dokumentasi. Teknik analisis data dalam penelitian ini, adalah reduksi data, penyajian data, interpretasi, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa terkait optimalisasi peran rimbawan muda dalam upaya pengelolaan kawasan konservasi TNGC tampaknya masih berbenturan dengan kebutuhan ekonomi masyarakat yang belum sepenuhnya tercukupi dengan beralih profesi menjadi pengelola wisata dan jasa lingkungan sejak Gunung Ciremai di tetapkan sebagai Taman Nasional. Terkait dengan implikasi optimalisasi peran rimbawan muda terhadap ketahanan wilayah, masih terdapat ketidakseimbangan di berbagai aspek seperti hak-hak masyarakat sekitar atas ekologi, ekonomi, sosial dan budaya di sekitar wilayah dan dari wilayah TNGC sendiri.